2019
DOI: 10.3390/medicina55090508
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory Fitness Cut-Points are Related to Body Adiposity Parameters in Latin American Adolescents

Abstract: Background and Objectives: A deficiency exists in the criterion-referenced cut-points for field-based cardiorespiratory fitness (CRF) in Latin American youths. The aims of the present study were two-fold: (1) To identify the ability of CRF estimated by the 20-m shuttle-run test (20mSRT) to differentiate between “healthy” and “unhealthy” phenotypes (by adiposity) in adolescents; (2) to assess the association between obesity and relative peak oxygen uptake (VO2peak) in a large and diverse sample of Latin America… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 32 publications
(39 reference statements)
2
13
0
Order By: Relevance
“…As the 20mSRT is a simple, low cost method of estimation CRF its use is urged at a population level, whilst using the CRF percentiles to allow stratification and effective identification of individuals in need of physical activity and fitness promotion. Additionally, these data of adolescents aged 13–15 years complement the study published by Prieto-Benavides et al [34] in the use of the Receiver Operating Characteristic analysis cut points to predict body adiposity parameters in practice by general practitioners, teachers, and coaches, may ensure that adolescents can be referred into intervention services effectively using a CRF assessment in a school setting.…”
Section: Discussionsupporting
confidence: 59%
“…As the 20mSRT is a simple, low cost method of estimation CRF its use is urged at a population level, whilst using the CRF percentiles to allow stratification and effective identification of individuals in need of physical activity and fitness promotion. Additionally, these data of adolescents aged 13–15 years complement the study published by Prieto-Benavides et al [34] in the use of the Receiver Operating Characteristic analysis cut points to predict body adiposity parameters in practice by general practitioners, teachers, and coaches, may ensure that adolescents can be referred into intervention services effectively using a CRF assessment in a school setting.…”
Section: Discussionsupporting
confidence: 59%
“…These effects could manifest in children and young people since the CRF had also been associated with cardiometabolic health and even mental variables [ 8 ]. It is desirable that this population group have adequate CRF levels; however, this variable has decreased in recent years in children and adolescents in Latin America [ 9 ]. Furthermore, it has been reported that physical inactivity in Chilean children and adolescents has reached over 80% [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Strong evidence indicates that excess weight during childhood is a predictor of future obesity and can increase cardiometabolic risks, such as insulin resistance, dyslipidemia, hypertension, and poor cardiorespiratory fitness, in obese children (Gepstein and Weiss, 2019;Wibaek et al, 2019). Emerging evidence also shows that cardiorespiratory fitness, as an important predictor of cardiovascular disease, not only helps prevent cardiovascular disease (Castro-Pinero et al, 2017;Kachur et al, 2017;Lavie et al, 2019) but also plays a regulatory role in reducing the risk of obesity in children (Lahoz-Garcia et al, 2018;Yu et al, 2018;Prieto-Benavides et al, 2019). Therefore, adverse changes in the aforementioned contributing factors will inevitably increase the risk of cardiometabolic diseases, such as type 2 diabetes and cardiovascular disease, in adulthood (Juonala et al, 2011;Chung et al, 2018).…”
Section: Introductionmentioning
confidence: 99%